اساليب المعاملة الوالدية وعلاقتها بالشعور بالأمن النفسي - عدواني, حنان; بوضياف, نادية (جامعة الوادي - University of Eloued, 2022)
يترتب على ولادة طفل ذو اعاقة او اكتسابه لها تدني ملحوظ في مجال او اكثر من مجالات الأداء او التكيف مع الواقع ،حيث يؤثر ذلك بشكل قوي على الطفل و كذلك على الاسرة، وبالتالي ستتبلور تحديات تواجه الاسرة في مواجهة هذا الاختلاف و تقبله و التعامل معه ، حيث ان الاعاقة تسبب ردود فعل نفسية مختلفة لدى الوالدين او افراد الاسرة الآخرين مما قد يحد من قدرتهم على دعم الفرد ذو الاعاقة و العناية به، ونظرا للضغوط والتحديات النفسية والاجتماعية التي يعايشها أباء هاته الفئة قد تتأثر اساليب المعاملة الوالدية عندهم ،وهذا ما ينعكس بالإيجاب او السلب على الشعور بالأمن النفسي الذي يعد احد اهم الحاجات النفسية للفرد على الاطلاق بصفة عامة و للفرد ذو الاعاقة على وجه الخصوص ، التي ينبغي اشباعها منذ الطفولة، والا فان الفرد سينشأ فاقدا له وبالتالي سيصبح عرضة للإصابة بالاضطرابات والمشكلات النفسية و الانفعالية وعليه جاء مقالنا ليبين اهمية هذين المتغيرين بالنسبة لفئة ذوي الاحتياجات الخاصة. Abstract The birth of a child with a disability or its acquisition of it leads to a marked decline in one or more areas of performance or adaptation to reality, as this strongly affects the child as well as the family, and thus challenges facing the family will crystallize in facing this difference, accepting it and dealing with it, As disability causes different psychological reactions to parents or other family members, which may limit their ability to support and care for the individual with disability, and given the psychological and social pressures and challenges that parents of this group experience, their parenting methods may be affected, and this is reflected positively or The robbing of the feeling of psychological security, which is one of the most important psychological needs of the individual at all in general and the individual with a disability in particular, which should be satisfied since childhood, otherwise the individual will grow up losing him and thus he will become vulnerable to psychological and emotional disorders and problems, and accordingly our article came to show the importance of These two variables are for the group with special needs.
لدى فئة ذوي الاحتياجات الخاصة نموذجا
مقال
Keywords: اساليب ؛ المعاملة الوالدية ؛ الامن النفسي ؛ ذوي الاحتياجات الخاصة; Parental treatment; Psychological security ; People with special needs.